Temporal bone partial ostectomy via the temporomandibular joint to treat osteosarcoma of the caudal zygoma in a three‐year‐old Labrador retriever. Issue 1 (22nd February 2016) - Dean, Barnaby Luke; Nicholson, Ian
Abstract : A three years, seven‐month‐old male entire Labrador retriever was referred with a one‐month history of pain when yawning and eating. CT revealed a 20×10×10 mm mass in the region of the left caudal zygoma. CT‐guided biopsy results identified a florid periosteal reaction but were otherwise inconclusive. Surgery was performed to resect the left caudal zygoma via the temporomandibular joint. Further histopathological results confirmed completely resected osteogenic osteosarcoma with narrow margins. No other treatment modalities were pursued. The dog remained free from clinical signs until 28 months following surgery when local tumour growth and thoracic metastases were diagnosed.